Respuesta :
[tex]rx + qx - d = gc \\rx + qx = d + gc \\x(r) + x(q) = d + gc \\x(r + q) = d + gc \\\frac{x(r + q)}{r + q} = \frac{d + gc}{r + q} \\x = \frac{d + gc}{r + q}[/tex]
When solving for x in rx + qx - d = gc, the solution is;
x = (gc + d)/(r + q)
This is about change in subject of formula in algebra.
We are given;
rx + qx - d = gc
We want to make x the subject of the formula.
Thus;
First step; Using addition property of equality, add d to both sides of the given equation to get;
rx + qx - d + d = gc + d
rx + qx = gc + d
Second Step; Factorize x out on the left hand side to obtain;
x(r + q) = gc + d
Third step; Using division property of equality, divide both sides by (r + q).
x(r + q)/(r + q) = (gc + d)/(r + q)
x = (gc + d)/(r + q)
Read more at; https://brainly.com/question/859191